Influence of different anodised nanoporous structures on the anti‐icing and electrical properties of transmission Al lines - Xu Dai; Yuan Yuan; Jie Xiao; Chenghao Jiang; Xujiang Hua; Huiying Xiang; Tao Zhu; Guoyong Liu; Jiang Zhou; Ruijin Liao (High Voltage)
Abstract Ice accumulation of overhead transmission lines can lead to serious damage to power systems. Superhydrophobic nanostructured Al conductors are proposed to replace the de‐icing or ice‐melting equipment for economic advantages, good anti‐icing properties and robust electrical performance. Anodisation under different direct current densities is adopted to fabricate two nanostructures on Al conductors, including the reticular and honeycomb‐like nanoporous structures. Compared to pure Al conductors, the anodised surface of honeycomb‐like nanoporous structures exhibits lower ice adhesion (3.82 kPa) and ice accumulation. Aluminium conductor steel reinforced treated in the proposed method has also been validated to exhibit a significant anti‐glaze icing property. Additionally, corona performance and line loss are experimentally measured and calculated to prove good electrical performance. The 0.27 A Al strand shows the highest corona inception voltage (27.86 kV) and the lowest AC resistance (4.65 Ω/km), which is attributed to the good dielectric property and heat dissipation. Therefore, the proposed anti‐icing transmission conductors show profound application potential for power systems.